INOVASI PROJECT-BASED LEARNING DALAM PEMBELAJARAN IPAS: STUDI KREATIVITAS SISWA PADA DIORAMA EKOSISTEM - Ike Prajayana, Marfita; Febriantika, Indah; Yayuk, Erna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science and Social Studies (IPAS) learning in elementary schools still faces challenges in fostering student creativity, particularly when the applied approaches do not actively engage students in contextual learning experiences. This study aims to describe the implementation of the Project-Based Learning (PjBL) model in the ecosystem topic and to analyze the forms of student creativity through a diorama project. The research employed a descriptive qualitative approach with 17 fifth-grade students of SDN 4 Mendenrejo in the 2024/2025 academic year as subjects. Data collection techniques included observation, interviews, and documentation. The study was conducted in four stages: (1) project and learning tool planning, (2) implementation of the ecosystem diorama project, (3) data collection, and (4) data analysis using Miles and Huberman’s model—comprising data reduction, data display, and conclusion drawing. The results show that the PjBL model fostered an active and meaningful learning environment. Students were directly involved in thinking, designing, and presenting their projects, which encouraged creativity in the form of original ideas, product innovation, the use of simple materials, and collaboration. A total of 94% of students demonstrated flexibility in material use, and all groups actively participated. This project not only improved students' understanding of ecosystem concepts but also enhanced creativity and 21st-century skills, making PjBL an effective and relevant approach for IPAS learning in elementary education.